Symbiosis Specificity of the Preceding Host Plant Can Dominate but Not Obliterate the Association Between Wheat and Its Arbuscular Mycorrhizal Fungal Partners - Campos, Catarina; Carvalho, Mário; Brígido, Clarisse; Goss, Michael J.; Nobre, Tânia (Frontiers in Microbiology, 2018)
Specificity of plant-host genotype is a key driver of arbuscular mycorrhizal fungi (AMF) communities. To clarify preferential associations between wheat (Triticum aestivum) and AMF and the effect of previous host and inoculum type (intact extraradicular mycelium (ERM) vs disrupted mycelium/spores), we studied AMF communities in the transition from Lolium rigidum, Ornithopus compressus, or a co-planting of both, to wheat, through sequencing of the LSU rDNA gene. Since the outcome of a specific host-symbiont interaction depends on the molecular responses of the host plant upon microbial colonization, the expression of six key symbiosis-related genes on wheat roots was also investigated. AMF communities on L. rigidum and O. compressus were clearly distinct. Under an undisturbed ERM, wheat AMF communities were similar to previous hosts, and O. compressus-wheat-AMF interactions matched a greater growth of wheat than L. rigidum-wheat-AMF interactions. This effect declined under disrupted ERM, generating also a greater activation of symbiotic genes in wheat, indicating that plant symbiotic program depends on some extent on the colonizing symbiont source. When L. rigidum and O. compressus were co-planted, the wheat colonisation pattern resembled that of O. compressus, although that was not reflected in a greater growth. Our data support the existence of a lasting effect of previous hosts in shaping wheat AMF communities through an efficient use of the established ERM, although partially retaining its host-symbiont specificity.